The differential diagnosis of adrenal incidentalomas with non-benign appearence on unenhanced computed tomography: a retrospective study - Irena A. Ilovayskaya; Anna Y. Lugovskaya; Alexey A. Glazkov; Timur A. Britvin; Larisa E. Gurevich; Valentina E. Shikina (Alʹmanah Kliničeskoj Mediciny)
Background: Сomputed tomography (CT) is considered as the gold standard for imaging the adrenal tumors. Tumor size and native density in unenhanced CT images are widely used to predict tumor malignancy, however, their diagnostic accuracy and the added value of clinical and anamnestic data remain uncertain.